Collapse of the Pickwick Club on Beach Street, July 5, 1925 - Campbell, W.W.K. (Tufts Archival Research Center, 2005)
Elevated view of the collapse of the Pickwick Club on Beach Street. Construction equipment and debris fills the area around the collapsed building. Construction workers are included in the photograph. Image included in Chinatown Banquet exhibit 8 1/16 x 6 1/8, 8 1/2 x 6 1/2 overall Photographs